SEMICONDUCTOR-DEVICES USING THE PLASMA-POLYMERIZED PYRROLE - PARK, SY; LEE, KP; CHOI, DH; KIM, NJ; SONG, SK (GORDON BREACH SCI PUBL LTD, 1994)
Organic semiconducting thin film of 10(-6) S/cm conductivity was prepared by the plasma polymerization of pyrrole followed by the thermal treatment in nitrogen. Obtained film (TPP-Py) was uniform, pin-hole free, and optically clear. We investigated the electrical and photoelectrical properties of the semiconductor devices consisting of the TPP-Py sandwiched between the two planar electrodes, such as the Au, Al, ITO, and n-Si. It was found that the TPP-Py formed ohmic contact with either Au or ITO electrode and showed a weak photoconducting behavior. On the other hand, the Schottky contact and heterojunction of TPP-Py with Al and n-Si respectively showed the rectification and photovoltaic properties. The performances of these cells were characterized in detail through the measurement of dark- and photoconductivity, and also of the capacitance-voltage (CV) characteristics.
Keywords: FIELD-EFFECT TRANSISTOR